Comparative Analysis of Maqashid Syariah Index Achievement at BPRS Muamalah Cilegon and BPRS Cilegon Mandiri After Covid-19 (2021–2023) - Rizka Khoirunnisa; Susilawati, Erni; Aisya Latifadinar (TSARWAH, 2025)
This study aims to compare the achievement of Maqashid Syariah Index (MSI) in two Sharia People's Financing Banks (BPRS) in Cilegon City, namely BPRS Cilegon Mandiri and BPRS Muamalah Cilegon, after the Covid-19 pandemic in the 2021-2023 period. The research method used is a comparative descriptive quantitative approach with secondary data analysis in the form of annual financial statements of the two BPRS and structured interviews with management. MSI measurement is carried out based on three main indicators, namely individual education, justice enforcement, and welfare improvement, which are adapted from the Abu Zahrah model and the Simple Additive Weighting (SAW) method. The results showed that BPRS Muamalah Cilegon consistently obtained a higher MSI score than BPRS Cilegon Mandiri, with an average MSI score of 0,62828 in the study period. This finding indicates that BPRS Muamalah Cilegon is more optimal in implementing maqashid sharia objectives, although both BPRS still have challenges in improving achievement in certain aspects. This study recommends the need to strengthen maqashid sharia-based strategies and program innovations for both BPRS in order to contribute more to the recovery and empowerment of the post-pandemic community economy.